Elevated remnant lipoproteins may increase subclinical CVD risk in pre‐pubertal children with obesity: a case‐control study. Issue 5 (13th December 2012) - Wang, Y.; Pendlebury, C.; Dodd, M. M. U.; Maximova, K.; Vine, D. F.; Jetha, M. M; Ball, G. D. C.; Proctor, S. D.
Summary: What is already known about this subject: Childhood obesity plays a fundamental role in the development of cardiovascular disease (CVD) and type 2 diabetes in adulthood. Clinical guidelines for the early management of CVD in children are poorly defined. Traditional cholesterol biomarkers such as low‐density lipoprotein cholesterol usually fall within the normal range in pre‐pubertal children with obesity. Remnant lipoproteins are overproduced by the intestine during obesity and type‐2 diabetes in adults and are an independent risk factor for CVD. What this study adds: Pre‐pubertal children with obesity have elevated (3‐fold) remnant lipoprotein concentration (assessed as apolipoprotein B48) relative to non‐obese controls, suggesting impaired metabolism of these atherogenic lipoproteins and potential increased CVD risk. Fasting apolipoprotein B48 is positively and significantly correlated with lipid biomarkers including triglyceride, total cholesterol and total cholesterol/high‐density lipoprotein cholesterol in pre‐pubertal children with obesity. Objectives: Current clinical guidelines to assess paediatric cardiovascular disease (CVD) risk heavily rely on cholesterol parameters that are generally normal for obese children. Remnant lipoproteins have emerged as a critical CVD risk factor particularly in adults with normolipidemia. We assessed remnant lipoprotein concentration (measured by apolipoprotein [apo] B48) and its relationship with other traditional CVD risk biomarkers in pre‐pubertal children with obesity. Methods: Pre‐pubertal children ( n  = 78) with obesity ( n  = 39, 9.9 ± 0.3 years old) as well as sex‐matched normal‐weight controls ( n  = 39, 9.8 ± 0.3 years) were assessed for anthropometry, blood pressure and fasting plasma biochemical parameters for remnant lipoprotein, lipid and glucose/insulin metabolism, and inflammatory status. Results: Children with obesity had striking 2‐fold higher apoB48‐containing remnant lipoproteins concentrations relative to normal‐weight peers; the magnitude of elevation in the remnant lipoproteins is comparable to the levels previously reported for adults with established CVD and type‐2 diabetes. Fasting apoB48 was positively correlated with fasting triglyceride concentration in children with obesity ( r  = 0.51, P  < 0.001) and their normal‐weight peers ( r  = 0.45, P  < 0.01). Traditional CVD biomarkers including low‐density lipoprotein cholesterol showed no difference between groups and remained within the normal range for a paediatric population. Conclusion: Elevated apoB48‐containing remnant lipoprotein is a stronger biomarker for paediatric CVD risk compared to traditional cholesterol parameters and may be associated with early adaptation of the intestine during obesity. Further investigation of abnormalities associated with the secretion and/or clearance of atherogenic remnant lipoproteins during the postprandial state may yield insight into our understanding of and therapeutic targets for managing risk for CVD in children with obesity.